Fishery and population characteristics of Indianmackerel, Rastrelliger kanagurta (Cuvier) atKakinada - Abdussamad, E M; Kasim, H Mohamed; Achayya, P (Indian Journal of Fisheries, 2011)
Indian mackerel, Rastrelliger kanagurta is exploited by trawls and gillnetsalong Kakinada coast. Its  production increased from 67 t in 1988 ’99 to 3,493t in 1997 ’98. Period of peak abundance and fishery was February-March whilerecruitment was high during  December-January. Length weight relationshipshowed that females were slightly heavier than males of the same size. Growthparameters, L∞ and K were estimated as 286.3 mm and 1.89/year respectively.Natural mortality of the stock was 2.61. Total mortality varied between 4.69and 9.29 and fishing mortality between 2.08 and 6.68. Stock varied during theperiod between 1,814 and 5,255 t and biomass between 268 and 902 t. Maxi-mum sustainable yield is 2,239 t. Emax is 0.77, whereas exploitation rate var-ied between 0.44 and 0.72. These indicated that the resource is currently un-der moderate fishing pressure especially from trawls and has only marginalscope for further increase in production. Since further increase in effort bytrawls would be detrimental for the resource it is recommended to reduce theireffort marginally or to maintain at the present level, whereas effort by gillnetscan be increased.